The Comparison of Nailfold Capillaroscopy between Juvenile Systemic Lupus Erythematosus and Healthy Controls: Correlation with Laboratory and Clinical Parameters - Seyed-Reza Raeeskarami; Navid Namazi; Raheleh Assari; Seyed-Reza Najafizadeh; Zohreh Hassannejad; Vahid Ziaee (International Journal of Vascular Medicine)
Background. Nailfold capillaroscopy is a noninvasive technique to recognize peripheral microangiopathy, which is an important feature in systemic lupus erythematosus (SLE). The aims of the present study were to investigate the prevalence of nailfold capillaroscopy (NFC) changes in juvenile systemic lupus erythematosus (JSLE), find out patterns of these changes, and correlate findings with clinical and laboratory parameters. Methods. Forty-nine patients with SLE, all meeting the 1997 revised ACR criteria for SLE classification, and 30 healthy controls were included. A digital video camera was used to capture nailfold capillary images. Computerized image processing was used for analysis. Results. Different abnormal NFC changes were observed with abnormal morphology, the increased diameter and abnormal loop densities in 55.1%, 93.9%, and 26.5% of the patients, respectively. No statistically significant differences were depicted between capillaroscopy with age, gender, autoantibodies (APLs, anti-ds DNA), antiphospholipid antibody syndrome, thrombotic angiopathy, renal function tests (Bun, Cr), and abnormal urine analysis. However, a significant correlation was found between the branched pattern and the CNS involvement group (P value <0.03). Conclusions. Different abnormal NFC changes are quite common among patients with SLE, and nailfold capillaroscopy is an effective method to monitor such changes. Treatment strategies may change in the branched pattern of nailfold capillaroscopy due to CNS involvement.